2022
DOI: 10.13005/bpj/2547
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cardiac Medications Induced QT Prolongation in Cardiac patients: A Retrospective Analysis

Abstract: Introduction: Cardiac patients are generally treated with cardiac medications but, when they develop other common conditions, they may have to be given the necessary non-cardiac medications. There are few such medications which, when given to the cardiac patients produces a potentially lethal drug interaction. Aim: The main aim of the study was to evaluate the prescription of non-cardiac medications that could cause QT interval prolongation among cardiac patients. Materials and methods: The medical records of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…[ 23 ] A meaningful study showed a significant association between education and self-medication practice. [ 24 , 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] A meaningful study showed a significant association between education and self-medication practice. [ 24 , 25 ]…”
Section: Discussionmentioning
confidence: 99%